Antibiotic and shared decision-making preferences among adolescents in Malaysia - Ngadimon, Irma Wati (Patient Prefer Adherence, 2015)
BACKGROUND: The purpose of this study was to establish baseline information on the current level of knowledge about, attitude toward, and experience with antibiotic usage, and preferences for shared decision making among adolescents in Malaysia. METHODS: A cross-sectional survey, involving 1,105 respondents who were aged between 13 and 17 years and who lived in Malaysia, was conducted using a validated questionnaire. The survey assessed knowledge, attitude, and experience with regard to antibiotic usage, and adolescents’ preferences for the style of shared decision-making process. RESULTS: The majority (n=786 [71.13%]) of the respondents had a low level of knowledge, 296 (26.79%) had a moderate level of knowledge, and 23 (2.08%) had a high level of knowledge. Further, they demonstrated a slightly negative attitude mean score of 3.30±0.05 (range: 0–8 points) but a positive experience mean score of 2.90±0.029 (range: 0–4 points). There was a positive correlation between knowledge and attitude scores, with a higher knowledge level associated with a more positive attitude toward antibiotic usage (r=0.257, P<0.001). Higher knowledge scores were associated with a more negative experience with antibiotic usage (r=−0.83, P=0.006). When assessing preference in shared decision making, more adolescents preferred an active role (n=408 [37%]) compared with collaborative (n=360 [32.6%]) or passive (n=337 [30.5%]) (P=0.028) roles. CONCLUSION: Current health care settings should involve adolescents in the decision-making process. Education packages can be introduced to improve adolescents’ knowledge of and practice of taking antibiotics, as well as to encourage their participation in decision making, in an attempt to reduce misuse of antibiotics.